Gulf Cooperation Council (GCC) : Labor Market Reforms to Boost Employment and Productivity in the GCC. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
The GCC growth model has delivered substantial improvements in living standards over several decades. Access to foreign labor has supported rapid growth in the non-oil sector and price stability in the region. It has also resulted in positive spillovers to the migrant-sending countries through large remittance flows. At the same time, governments have increased public-sector employment and have helped raise standards of living. However, the growth model has involved costs: the public-sector wage bill is relatively high, there is limited employment of nationals in the private sector, labor productivity has declined or stagnated, and there is limited progress on economic diversification.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet